2023
DOI: 10.3390/ma16145114
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of PLA Sheets Prepared by Stretching under Different Conditions: Influence of Reprocessing and Establishing Optimal Conditions

Abstract: Polylactide (PLA) is one of the most commonly used biomaterials nowadays, with many recognized benefits, particularly in the packaging and single-use products industries. However, little research has been conducted on its stretching behavior. This work investigates the optimal conditions of biaxial stretching of injection-molded PLA samples produced under different processing conditions (pressure, drying, and pre-processing by extrusion, to simulate a recycling step). The injection-molded samples were characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The double-ln plot was obtained by tting equation in the range of 20-80% for X t [43], which attributed to the deviation from linearity due to crystal competition that occur at the beginning and end of crystallization [44]. As shown in Table 4, the n value of PLA systems at different T c between 2 and 4, this suggested that crystal nucleation was sporadic and instantaneous.…”
mentioning
confidence: 94%
“…The double-ln plot was obtained by tting equation in the range of 20-80% for X t [43], which attributed to the deviation from linearity due to crystal competition that occur at the beginning and end of crystallization [44]. As shown in Table 4, the n value of PLA systems at different T c between 2 and 4, this suggested that crystal nucleation was sporadic and instantaneous.…”
mentioning
confidence: 94%